How Islamic and conventional bank in Indonesia contributing sustainable development goals achievement - Nunung Ghoniyah; Sri Hartono (Cogent Economics & Finance, 2020)
This study aimed to prove that social goal in improving social living standards is implanted on banking's objective in Indonesia. This research also tried to prove that there were differences between conventional and Islamic banks in defining the company goals, whether the goals are profit-oriented or socially oriented. This social goal is also aligned with sustainable development goals (SDGs) as international agendas in the world. The banks' contribution will be measured its impact on sustainable development goals. The developed hypotheses are equipped with good financing quality control. Furthermore, this research will compare the social goals of conventional banks and Islamic banks (sharia banks). This research used 801 data from the annual reports of conventional and Islamic banks in Indonesia from 2011 to 2018. Meanwhile, the reflection of sustainable development goals used several indicators, so that the statistical analysis used is WarpPLS. This research proved that there were differences between Islamic and conventional banks in promoting sustainable development. Generally, high financing or credit will increase sustainable development, while the sufficient/low bank profit demanded from the bank financing/credit also will increase sustainable development achievement. In conclusion, the financing quality is able to differentiate whether the low profits earned by banks are due to social orientation for sustainable development or because of poor market conditions (bad credit/financing).
Keywords: 330; credit distribution; social living standards improvement; sustainable development goals; the goal and function of bank